Study of the Functional State of the Left Ventricular Myocardium in Patients with Coronary Artery Disease with Impaired Metabolism of Homocysteine and Vitamin D - Nikonenko, O. S.; Nikonenko, A. O.; Chmul, K. O.; Molodan, O. V.; Osaulenko, V. V. (Ukrainian Journal of Cardiovascular Surgery, 2020)
To date, it has been established that in the progression of coronary artery disease (CAD) and its complications, an increase in the level of homocysteine and hypovitaminosis D are essential. However, medical publications do not adequately cover the study of the effects of hyperhomocysteinemia and vitamin D deficiency on the course of atherosclerosis and the functional state of the myocardium, and requires more detailed research of this problem. Objective. To study the functional state of the myocardium depending on the degree of hyperhomocysteinemia and hypovitaminosis D in patients with CAD. Materials and methods. The study analyzed data from 69 diagnosed with CAD. Depending on the degree of hyperhomocysteinemia and the level of vitamin D, patients were divided into 3 groups. Results. In all patients, speckle-tracking echocardiography revealed a decrease in longitudinal and circular myocardial deformation. Patients with hyperhomocysteinemia and vitamin D deficiency had significantly lower myocardial deformity. Comparing the data of echocardiography, it was found that in patients of all three groups – no significant difference in hemodynamic parameters was found, despite the difference in the level of HC and vitamin D. Conclusions. Hyperhomocysteinemia and hypovitaminosis D are risk factors for the development of CAD. It was revealed that the higher level of homocysteine and the pronounced deficiency of vitamin D, are associated with more pronounced changes in the functional state of the myocardium.